The Diane Goode Book of American Folk Tales & Songs - Goode, Diane; Durell, Ann. (New York : E.P. Dutton, 1989)
Presents a collection of folk tales and songs from a variety of regions and ethnic groups in the United States.
Keywords: Tales -- United States; Folk songs, English -- Juvenile literature. -- United States; Folklore -- United States; Folk songs, English -- United States; Folk-songs, English -- Juvenile literature. -- United States